EFFECT OF INCISOR INCLINATION CHANGES ON CEPHALOMETRIC POINTS A AND B - Hassan, Sohaib; Shaikh, Attiya; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2015)
Background: The position of cephalometric points A and B are liable to be affected by alveolar remodelling caused by orthodontic tooth movement during incisor retraction. This study was conducted to evaluate the change in positions of cephalometric points A and B in sagittal and vertical dimensions due to change in incisor inclinations. Methods: Total sample of 31 subjects were recruited into the study. The inclusion criteria were extraction of premolars in upper and lower arches, completion of growth and orthodontic treatment. The exclusion criteria were patients with craniofacial anomalies and history of orthodontic treatment. By superimposition of pre and post treatment tracings, various linear and angular parameters were measured. Various tests and multiple linear regression analysis were performed to determine changes in outcome variables. Statistically significant p-value was ‰¤0.05. Results:One-sample t-test showed that change in position of only point A was statistically significant which was 1.61mm (p<0.01) in sagittal direction and 1.49mm (p<0.01) in vertical direction. Multiple linear regression analysis showed that if we retrocline upper incisor by 10o, the point A will move superiorly by 0.6mm.Conclusions: Total change in the position of point A is in a downward and forward direction. Total Change in upper incisors inclinations causes change in position of point A only in vertical direction. Keywords: Incisor inclination, Point A, Point B, cephalometric